Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Dengan Reputasi Sebagai Intervening - Abdussalam, M Ilham; Animah, Animah (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
CSR performance will be better if the company has a good reputation, which basically has a positive relationship with the company's financial performance. The aim of this research is to determine the effect of CSR on financial performance and the company's reputation as an intervening agent. The method used is quantitative. Total observation in this study were 88. Datas were obtained from annual reports and were analyzed with IBM SPSS Statistics 26. The results of this research are (1) CSR disclosure has an influence on the company's financial performance. (2) CSR disclosure has no influence on the company's reputation. (3) Company reputation has a positive effect on financial performance